Design and Implementation of an Autonomous Service Robot for Hospital Isolation Room Using Robot Operating System 2 and Navigation 2 - Muhammad Nurul Puji; Dwinandana, Tubagus Ahmad; Kasih, Tota Pirdo; Lee, Edmond; Kamalo, Giovanni Benedict Davin; Anthony, Patrick; Kunaifi, Matthew (Universitas Ahmad Dahlan, 2024)
Healthcare-associated infections or nosocomial infections are infections that are acquired after admission to a hospital. This type of infection extends the length of stay, increases the cost of healthcare, and increases the mortality rate. This infection is caused by pathogens that are present in the hospital environment. These pathogens are transmitted when a hospital worker comes in contact with a patient or their environment. Thus, it is important to reduce the contact between them to stop the spread of pathogens. To reduce contact an autonomous service robot is utilized to deliver food or medicine to patients. This robot will be able to go to multiple target positions autonomously and will be controlled by a web application. Furthermore, the robot can provide a video call if the patient needs help. The robot platform used is the turtlebot3 and the software framework used is robot operating system 2 humble. The inflation radius and cost scaling parameters are tuned to increase the navigation success rate. Problems encountered during testing include glass windows not being detected by lidar, noisy lidar data, and obstacles being too low to be detected. These problems are solved using tape, costmap and laser filter, and keepout zones respectively. To evaluate the performance and capability of the app the robot is tested using a set of target locations entered on the app. During testing poor odometry causes localization error that causes recovery behaviors. The final system has a navigation success of 95%, with an average navigation speed of 0.17 m/s, and an average distance to target of 0.0587 m.